A Novel TetR-Like Transcriptional Regulator Is Induced in Acid-Nitrosative Stress and Controls Expression of an Efflux Pump in Mycobacteria - Perrone, Filomena; De Siena, Barbara; Muscariello, Lidia; Kendall, Sharon L.; Waddell, Simon J.; Sacco, Margherita (Frontiers in Microbiology, 2017)
Mycobacterium tuberculosis has the ability to survive inside macrophages under acid-nitrosative stress. M. tuberculosis Rv1685c and its orthologue in M. smegmatis, MSMEG_3765, are induced on exposure to acid-nitrosative stress. Both genes are annotated as TetR transcriptional regulators, a family of proteins that regulate a wide range of cellular activities, including multidrug resistance, carbon catabolism and virulence. Here we demonstrate that MSMEG_3765 is co-transcribed with the upstream genes MSMEG_3762 and MSMEG_3763, encoding efflux pump components. RTq-PCR and GFP-reporter assays showed that the MSMEG_3762/63/65 gene cluster, and the orthologous region in M. tuberculosis (Rv1687c/86c/85c), was up-regulated in a MSMEG_3765 null mutant, suggesting that MSMEG_3765 acts as a repressor, typical of this family of regulators. We further defined the MSMEG_3765 regulon using genome-wide transcriptional profiling and used reporter assays to confirm that the MSMEG_3762/63/65 promoter is induced under acid-nitrosative stress. A putative 36 bp regulatory motif was identified upstream of the gene clusters in both M. smegmatis and M. tuberculosis and purified recombinant MSMEG_3765 protein was found to bind to DNA fragments containing this motif from both M. smegmatis and M. tuberculosis upstream regulatory regions. These results suggest that the TetR repressor MSMEG_3765/Rv1685c controls expression of an efflux pump with an, as yet, undefined role in the mycobacterial response to acid-nitrosative stress.